Compound odontoma and tooth retention in a pediatric patient: Clinical case report carried out in the municipality of Balsas-MA (Research, Society and Development, 2023)
The compound odontoma, classified as an odontogenic tumor, with the highest incidence rates, representing up to 70% of all odontogenic tumors found. It is a benign tumor, composed of odontogenic epithelium with odontogenic ectomesenchyme. Its histology presents with different dental tissues, including enamel, dentin, cementum, and, in some cases, pulp tissue. Therapy consists of surgical excision. This case report aimed to describe the step-by-step surgical procedure for removing a compound odontoma in a pediatric patient, and thereby emphasize the importance of early and conclusive diagnosis, as well as its treatment plan. An 8-year-old male patient with the absence of eruption of teeth 11 and 12 and prolonged retention of tooth 52. The diagnosis and surgical procedure were thorough and precise. During the patient's 7-month follow-up, there was no spontaneous eruption of the teeth. Therefore, diagnosing and investigating clinical, radiographic, and tomographic situations suggestive of odontomas are essential to avoid damage to the permanent dentition and the timeline of tooth eruption.